2023
DOI: 10.3389/fped.2023.1108788
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of a predictive nomogram for the risk of premalignant lesions in children with choledochal cyst

Abstract: BackgroundCholedochal cyst (CDC) increases the risk (2.5%–30%) of malignancy. Metaplasia and dysplasia have been recognized as premalignant lesions among CDCs. This study aimed to evaluate the risk factors of metaplasia and dysplasia in CDC children.MethodsTwo hundred and ten CDC children who underwent cyst excision and Roux-en-Y hepaticojejunostomy at our institution between July 2020 and November 2021 were included and randomly divided into the training set and validation set. Univariate and multivariate log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Ono et al also reported signi cantly higher Ki-67 labeling index in the gallbladder mucosa of children with CDC than that in controls, suggesting mucosa changes could be initiated from early childhood [16]. In a study involving 210 children with CDC, epithelial premalignant lesions, including intestinal metaplasia, pyloric gland metaplasia, and low-grade dysplasia, were identi ed in 78(37.1%) cases [17].…”
Section: Discussionmentioning
confidence: 99%
“…Ono et al also reported signi cantly higher Ki-67 labeling index in the gallbladder mucosa of children with CDC than that in controls, suggesting mucosa changes could be initiated from early childhood [16]. In a study involving 210 children with CDC, epithelial premalignant lesions, including intestinal metaplasia, pyloric gland metaplasia, and low-grade dysplasia, were identi ed in 78(37.1%) cases [17].…”
Section: Discussionmentioning
confidence: 99%